Idiopathic Bilateral Simultaneous Facial Nerve Palsy (B-FNP) - Theresia Christin; Ratri Wulandari; Luther Theng; Selly Marisdina (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Background: Bilateral facial nerve palsy (B-FNP) is a rare clinical manifestation with incidence of 1 per 5 million people. Furthermore, it approximately accounts for 0.3 – 2 % of facial palsy cases. This B-FNP case is intricate in the diagnosis, finding the aetiology, and treatment that need hospitalization. Case Report: A male 64-year-old with bilateral facial nerve palsy that happened suddenly followed by difficulty in closing both eyes and facial abnormality without clear cause within 7 days of onset. Risk factor is hypertension stage 2. During neurological examination, there was bilateral peripheral facial nerve palsy grade IV in right side and grade III in the left side (House Brackmann grading system) that was not followed by other cranial nerve abnormality and motoric examination is normal. Supporting examinations such as lumbar puncture, thorax photo, and head MRI with contrast shows normal result. ENMG examination shows absent of blink reflex. Prednisone 60 mg orally was given with tapering off dosage 10 mg per day. Patient was hospitalized for 12 days and was discharge with good clinical improvement with bilateral peripheral facial nerve paralysis grade II in right side and grade I in left side. Conclusion: Bilateral facial nerve paralysis is a rare clinical manifestation and challenging in diagnosis. It is important to have a differential diagnosis in cases with bilateral cranial nerve palsy. Careful physical examination and appropriate supporting examinations such as laboratory and radiology in necessary to evaluate the underlying cause.